2017
DOI: 10.3390/su9091628
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic and Spiritual Ecosystem Services Provided by Urban Sacred Sites

Abstract: Abstract:The range and use of ecosystem services provided by urban sacred sites has hardly been considered in studies of urban ecology, sustainability and human wellbeing. This paper examines the perceived ecosystem services supplied by green spaces or gardens associated with places of religious worship and appreciated by worshippers in a mid-sized town in South Africa. A questionnaire with open, closed and Likert scale questions was administered at 30 places of worship (25 with gardens and five without). Resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 54 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…These provide public health professionals with further opportunities to provide advice and interventions for improving the health of vulnerable communities. Interestingly, De Lacy and Shackleton (2017) reported that greenspace associated with urban sacred sites enhanced the spiritual experience of visitors. Nature is deeply embedded into a number of religions, therefore spending time in nature enhances a sense of belonging and the spiritual experience (Lindgren et al 2018).…”
Section: Aesthetic Appreciation and Spiritual Well-beingmentioning
confidence: 99%
“…These provide public health professionals with further opportunities to provide advice and interventions for improving the health of vulnerable communities. Interestingly, De Lacy and Shackleton (2017) reported that greenspace associated with urban sacred sites enhanced the spiritual experience of visitors. Nature is deeply embedded into a number of religions, therefore spending time in nature enhances a sense of belonging and the spiritual experience (Lindgren et al 2018).…”
Section: Aesthetic Appreciation and Spiritual Well-beingmentioning
confidence: 99%
“…They also have economic values such as being sources of food, nutrition supplement, fuelwood and animal fodder (Agbelade et al, 2017). Another important value of African urban trees and forests pertains to spirituality and cultural attachments (La Rosa, Spyra, & Inostroza, 2016;Peter & Shackleton, 2017;Sheona et al, 2015). Some trees are attached to spirits or serve as shrines for worships (Babalola et al, 2013;Oyebade, Popo-ola, & Itam, 2013) and therefore serve as connections between urban dwellers and various divinities.…”
Section: Values Of Urban Trees and Forests In Africamentioning
confidence: 99%
“…Other environmental aestheticians, such as Hepburn [36], believed that the full-body immersion of viewer marks a substantial difference between the experiences of appreciating nature and appreciating art. Unlike the detached mode of appreciation in viewing art, in natural settings, people are absorbed extensively and therefore more easily evoke metaphysical imagination [15,[36][37][38][39][40]. In fact, an innate connectedness to nature is the state of mind that one can develop when interacting with nature [41,42].…”
Section: Nature As a Source Of Aesthetic Experiencementioning
confidence: 99%